Potential of bioenergy production from industrial kenaf (Hibiscus cannabinus L.) based on Malaysian perspective. (February 2015) - Saba, N.; Jawaid, M.; Hakeem, K.R.; Paridah, M.T.; Khalina, A.; Alothman, O.Y.
Abstract: Nowadays, the energy requirement of increasing population is creating energy crisis, and it's become a serious and alarming thread for sustainability of natural resources. Moreover, upcoming demand of energy requirement is growing faster in developing countries as compared to developed ones. Malaysia is one of the fastest growing, developing countries, which is experiencing drastic and regular growth in population and economy in the recent years. It is an urgent requirement for the government and policy makers to explore alternative energy sources to accomplish upcoming demands of a growing population in the form of energy sufficiency. Malaysia is blessed with tropical and sub-tropical climates, which are suitable for exploring the green agriculture and forest potential. Most of the available energy resources in the form of fossil fuels have already been explored, and it is expected that energy demand will grow continuously by two to three fold in the next decades. Biomass resource is abundant in Malaysia. This can be considered as an alternative source of renewable and sustainable energy, with a promising future to fulfil continuous and uninterrupted supply of energy. Agricultural biomass such as Industrial Kenaf ( Hibiscus cannabinus L.) has been successfully investigated as a great potential to be used as a renewable and sustainable feedstock for the production of bio-energy. Kenaf regarded as a traditional crop of Malaysia. Kenaf biomass would appear as a potential material for great sustainable energy (bioethanol, biohydrogen, bioenergy) supplier in the coming future. In this review, we have provided an insight of kenaf biomass, its morphology, structure, chemical compositions, storage and sowing, cultivation, harvesting, yield and different sustainable energy possible to get from it. We also discuss the feasibility of kenaf biomass as a sustainable energy source supplier in Malaysian prospective.